Hernia Inguinalis Lateralis Bilateral Irreponible : A Case Report - Abdillah A.F Hasanusi; Jacky Tuamelly (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Inguinal hernia is one of the most common abdominal wall disorders, accounting for approximately 75% of all hernia cases, with 50% classified as lateral inguinal hernias, and it occurs more frequently in older adults. We report a 57-year-old male patient who was admitted to the hospital with a complaint of a lower abdominal mass. The mass initially appeared in the right inguinal region one year prior and subsequently developed in the left inguinal region two months later. The swelling progressively increased in size. Intermittent pain, predominantly on the left side, had been present for the past month without associated nausea, vomiting, or fever. Physical examination revealed a moderately ill general condition, stable vital signs, and a soft, tender mass in both inguinal regions. Based on the clinical history, physical examination, and supporting investigations, the patient was diagnosed with bilateral irreducible lateral inguinal hernia. The patient received intravenous Ringer’s lactate and intravenous ketorolac, followed by an elective herniorrhaphy using Lichtenstein Tension-Free Repair Technique under spinal anesthesia. The operation was completed successfully without intraoperative complications.